Cutaneous Angiosarcoma of the Foot: A Case Report and Review of the Literature - Sharang Tenjarla; Lucy Ashley Sheils; Theresa M. Kwiatkowski; Sheema Chawla (Case Reports in Oncological Medicine)
Primary Angiosarcoma of the skin of the foot is very rare. Angiosarcoma is typically treated with resection and wide-field postoperative radiation therapy. Chemotherapy and radiation therapy have also been used. Regardless of the treatment, the risk of local and distant relapse remains high for this disease. We present a case of an elderly patient who developed cutaneous angiosarcoma of the foot. It posed as a diagnostic dilemma at presentation. Chronic lymphedema was a possible predisposing factor. Given his age, preexisting renal dysfunction, refusal of surgery, and preference not to receive chemotherapy, the patient was ultimately treated with definitive radiotherapy. We present this case because of its rare site, unique presentation and delay in diagnosis of the condition, and attainment of an excellent response to radiation at the time of follow-up. We also review the current literature on this topic.